Perceived Quality, Brand Trust, Image, and Loyalty as Key Drivers of Fast Food Brand Equity - Ole, Hizkia C.; Sakka, Eirene W. M.; Mandagi, Deske W. (Indonesian Journal of Islamic Economics and Finance, 2025)
In the fiercely competitive fast-food industry, building strong brand equity is crucial for long-term success. This study investigates the effects of brand trust, brand image, and perceived quality on brand equity, while also examining the mediating role of brand loyalty in these relationships within the context of fast-food restaurants. Employing a quantitative, descriptive, and correlational research design, this study explores the interrelationships among these variables. Data were collected through a structured questionnaire administered to 175 regular customers of fast-food restaurants in North Sulawesi, Indonesia. The collected data were analyzed using Structural Equation Modeling (SEM) with the aid of SmartPLS statistical software. The findings reveal that brand image and perceived quality are the primary determinants of brand equity, exerting both direct and indirect effects through the mediating role of brand loyalty. However, brand trust does not significantly influence either brand loyalty or brand equity. The study’s focus on a specific geographic region limits the generalizability of the findings to a broader population. Furthermore, the measurement instruments employed may not comprehensively capture the emotional and functional dimensions of brand trust, which could affect the validity of the results. This study contributes to the field of brand management and the fast-food industry by providing insights into the critical factors shaping brand equity. The findings offer valuable implications for both academics and practitioners seeking to enhance brand equity through strategic brand management initiatives.